Existential Supervision: Phenomenological Research (Existential Analysis: Journal of the Society for Existential Analysis, 2017)
This paper presents phenomenological research the aim of which is to describe supervision in a structural way from the existential–phenomenological perspective by distinguishing its characteristic features. The research is based on a description of the experience of 12 research participants acting as supervisees and supervisors. The results are summarised in two definitions. The research has revealed four dimensions of the phenomenon, three of which coincide from both the research participants' positions: the peculiarities of the supervision process, the way of the supervisor's presence and the relationship between the supervisor and the supervisee have been distinguished as important characteristics of existential–phenomenological supervision by the research participants. The way in which the supervisor is present has been named as one of the most important characteristics of existential–phenomenological supervision by the research participants acting as supervisees. Meanwhile the research participants acting as supervisors placed stronger emphasis on the supervision process itself. The way in which the supervisor is present has been named as one of the most important characteristics of existential–phenomenological supervision by the research participants acting as supervisees. Meanwhile the research participants acting as supervisors placed stronger emphasis on the supervision process itself. The result of the supervision as a sensuous change and not the reception of a mental answer has been described as an important feature of phenomenological supervision. Meanwhile research participants acting from a supervisor's position described interventions used in the supervision as an important, however, least frequently met characteristic of existential–phenomenological supervision.
Keywords: Existential–phenomenological supervision; supervisor; phenomenological research.